Enhancing biofuel pellet quality using torrefaction and co-pelletization of palm kernel shell and empty fruit bunch - Sang, Chang Siaw; Suriyati, Saleh; Noor Asma Fazli, Abdul Samad (Springer Nature, 2025)
Palm kernel shell (PKS) and empty fruit bunch (EFB) are potential biomass resources for producing solid biofuel for energy applications. However, raw EFB and PKS are not uniform in size and pose rotting behavior. Torrefaction and co-pelletization are both effective methods to improve their combustion and mechanical characteristics. This study aims to investigate the effect of torrefaction temperature and the blending ratio of PKS and EFB on the mechanical and combustion characteristics of co-pellets. Initially, PKS and EFB underwent torrefaction process for 30 min at three different temperatures (210 °C, 240 °C, and 270 °C). Then, both torrefied PKS and EFB were blended at five different ratios (0:100, 25:75, 50:50, 75:25, 100:0) with carboxymethyl cellulose as a binder (10% by weight). The results showed that pellet produced at higher torrefaction temperature at 270 °C resulted in an increment of the higher heating value (HHV) but weaker mechanical strength. Pellet with a blending ratio of PKS to EFB (75:25) torrefied at 240 °C showed the comparatively best pellet quality in terms of HHV (17.94 MJ/kg), high tensile strength (3.5 MPa), low ash content (3.97 wt%), and the lowest density changes (0.66%), which satisfy the standard requirements for commercial pellets, indicating that a high-quality biofuel pellet can be produced using torrefaction and co-pelletization.